Experiences of families that have children with mental disorders - Eliane Rosso; Miriam Aparecida Nimtz; Marcio Roberto Paes; Mônica Mello de Macedo Ignácio; Mariluci Alves Maftum; Camila Bonfim de Alcantara (Universidade Federal de Santa Maria, 2020)
Objective: to describe the experiences of members of families that have children with mental disorders. Method: qualitative research, with the hybrid oral thematic history method carried out with eight family members in a Specialized Educational Service Center. Data were collected from March to May 2017, via semi-structured interviews. Results: two categories emerged: Emotions, feelings and difficulties experienced by family members of children with mental disorders; and, Support for family, social and health support for children with mental disorders. The family reported tiredness, exhaustion, guilt and insecurity, revealing important changes in the family dynamics following the diagnosis of mental disorder. Final considerations: family members lack information about mental disorders; need to adapt the family routine to attend to the child; and require support from family, friends, teachers and other professionals so that they can take care of their child.